A methodology for fast assessments to the electrical activity of barrel fields in vivo: from population inputs to single unit outputs - Riera, Jorge J.; Goto, Takakuni; Kawashima, Ryuta (Frontiers in Neural Circuits, 2014)
Here we propose a methodology to analyze volumetric electrical activity of neuronal masses in the Wistar somatosensory barrel field. The key elements of the proposed methodology are a three-dimensional microelectrode array, which was customized by our group to observe extracellular recordings from an extended area of the barrel field, and a novel method for the current source density analysis. By means of this methodology, we were able to localize single barrels from their event-related responses to single whisker deflection. It was also possible to assess the spatiotemporal dynamics of neuronal aggregates in several barrels at the same time with the resolution of single neurons. We used simulations to study the robustness of our methodology to unavoidable physiological noise and electrode configuration. We compared the accuracy to reconstruct neocortical current sources with that obtained with a previous method. This constitutes a type of electrophysiological microscopy with high spatial and temporal resolution, which could change the way we analyze the activity of cortical neurons in the future.